Brief Report: Context Matters. (15th December 2017) - Haberer, Jessica E.; Ngure, Kenneth; Muwonge, Timothy; Mugo, Nelly; Katabira, Elly; Heffron, Renee; Musinguzi, Nicholas; Bangsberg, David R.; Celum, Connie; Baeten, Jared M.
Abstract : Background: Short message service (SMS) surveys are a promising tool for understanding whether preexposure prophylaxis (PrEP) adherence aligns with risk for HIV acquisition—a concept known as prevention-effective adherence. Methods: The Partners Demonstration Project was an open-label study of integrated PrEP and antiretroviral therapy (ART) delivery among high-risk HIV serodiscordant couples in East Africa. HIV-uninfected partners were offered PrEP until their HIV-infected partner had taken ART for ≥6 months. At 2 study sites, HIV-uninfected partners were offered enrollment into the Partners Mobile Adherence to PrEP (PMAP) substudy based on ongoing PrEP use, personal cell phone ownership, and ability to use SMS. SMS surveys asked about PrEP adherence and sexual activity in the previous 24 hours; these surveys were sent daily for the 7 days before and 7 days after routine study visits in the Partners Demonstration Project. Results: The PMAP substudy enrolled 373 HIV-uninfected partners; 69% were men and mean age was 31 years. Participants completed 17, 030 of 23, 056 SMS surveys sent (74%) with a mean of 47 surveys per participant over 9.8 months of follow-up. While HIV-infected partner use of ART was <6 months, mean reported PrEP adherence was 92% on surveys concurrently reporting sex within the serodiscordant partnership, and 84% on surveys reporting no sex ( P < 0.001). Discussion: SMS surveys provided daily assessment of concurrent PrEP adherence and sexual behavior. Higher PrEP adherence was temporally associated with increased risk for HIV acquisition. Abstract : Supplemental Digital Content is Available in the Text.